THE ANALYSIS OF CONSUMER SATISFACTION TOWARD GO-PAY FIN-TECH SERVICE AT FACULTY OF ECONOMICS AND BUSINESS STUNDENTS AT CHRISTIAN UNIVERSITY OF INDONESIA - Sembiring, Carolina F.; Tambunan, Juniaty (Universitas Kristen Indonesia, 2019)
The study was conducted at the Faculty of Economics and Business of the Christian University of Indonesia to know customers satisfaction and expectations as well as the implementation or performance of the company. In providing good services to customers, GO-JEK companies must pay attention to the variables that become this research, namely five dimensions of service quality, among others tangiable, responsiveness, assurance, realibility, and emphaty. GO-JEK management needs to pay attention to comfort and security in every transaction on the GO-PAY application. Keywords: Cunstomer satisfaction, The Importance and Performance Analysis, Fin-Tech GO-PAY